Polyamide-11 composites reinforced with cellulosic materials - Kattamanchi, Tanuj (My University, 2021)
The study presents the methods of developing bio sourced polyamide (PA11) composite reinforced with sustainable cellulose nanocrystals (CNC) or pulp fibres for a high-performance composite material. The reinforcement based on cellulose in thermoplastic composites at industrial scale thus far has been difficult due to the high temperatures to which the materials are being exposed during their melt processing. Commercially available cellulosic materials are highly sensitive and underperform at high temperatures. The work presented here provides large scale industrially viable method for producing composites that preserve the cellulose from excessive thermal degradation at increasing weight percentages of reinforcement (up to 40 wt.%) and includes assessment of the reinforcement effect provided by a pilot scale produced acetylated pulp fibres. Results indicate that modified fibres and wet feeding strategy contribute to improve the fibres dispersion, so enhancing the mechanical performance of the composites. This work contributes to the knowledge that can enable the melt processing of high-performance cellulose reinforced composites towards a large-scale industrial manufacturing
Keywords: polyamide 11; CNC; pulp fibres; melt processing; thermo-mechanical characterization